The exposure routes of micro- and nanoplastics and their potential toxic effects on human health - Dorota Sawicka; Luiza Chojnacka-Puchta; Lidia Zapór; Katarzyna Miranowicz-Dzierżawska; Jolanta Skowroń (Nofer Institute of Occupational Medicine, 2024)
This article discusses the classification of micro- and nanoplastics (MNP), the routes of their exposure and the effects of MNP on the reproductive, respiratory, digestive and immune systems based on in vitro and in vivo studies, as well as available epidemiological data. The MNP can enter our body through inhalation, food or skin. The presence of microplastics (MP) in tap, bottled and deep sea water, as well as in sea salt, fruit and vegetables has been demonstrated. Due to their small size, MNP can be absorbed and easily distributed through the blood and lymphatic vessel system to tissues and organs. Recent studies have provided evidence of the accumulation of MNP in human lungs and even in the placenta. The accumulation of MNP in the body may have long-term effects and lead to health problems in humans, such as bronchitis, development of asthma, pulmonary fibrosis, inflammation and cancer. The information included in the article gives partial insight into how MNP may affect the human body. However, to fully assess the toxicity of MNP, comprehensive research is necessary, including standardization of MNP detection techniques and determination of the MNP content in food and water. It is also advisable to assess toxicokinetic parameters, as well as to determine the daily dose of exposure and interaction of MNP with various cells. Insufficient data on direct exposure to MNP in the work environment, as well as in other public places, constitutes a factor hindering the establishment of appropriate legal standards. In 2024, work on establishing the first act of EU law enabling the monitoring of MP in drinking water should be completed, which raises great hopes that in the future limit values for MNP in water and food and in workplaces will also be established. Med Pr Work Health Saf. 2024;75(1):81-96